DYKE PROPAGATION WITH DISTRIBUTED DAMAGE OF THE HOST ROCK - Mériaux C.; Lyakhovsky V.; Agnon A.; Lister J.R. (My University, 1999)
Observations of off-plane inelastic deformation around dykes motivate consideration of models of fluid-driven crack propagation in a solid which can undergo material degradation, or damage. The application to dyke propagation of a recently proposed damage rheology [Lyakhovsky et al., J. Geophys. Res. 102 (1997) 27635–27649] based on thermodynamical principles and experimental measurements is discussed. The rate of accumulation of damage in this rheology is the product of a material-dependent parameter cd and the square of the strain. For geological values, a dimensionless parameter cdη/ΔP characterizing the ratio of a damage timescale to a flow timescale is very small, where η is the magmatic viscosity and ΔP the driving pressure. As a result, significant rates of damage are confined to a small region near the dyke tip, where the strain is large. Consideration of possible singularities in near-tip solutions, shows that the rate of propagation is governed by the viscous fluid mechanics. To a good approximation, the rate has a value equal to that given by the zero-stress-intensity solutions of previous models based on linear elastic fracture mechanics. Predictions from the damage rheology both of a narrow damage zone and of the rate of propagation are in good agreement with observations.